2015
DOI: 10.1007/s00267-015-0447-7
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation and Forest Fires in Roraima and Their Relationship with Phytoclimatic Regions in the Northern Brazilian Amazon

Abstract: Deforestation and forest fires in the Brazilian Amazon are a regional-scale anthropogenic process related to biomass burning, which has a direct impact on global warming due to greenhouse gas emissions. Containment of this process requires characterizing its spatial distribution and that of the environmental factors related to its occurrence. The aim of this study is to investigate the spatial and temporal distribution of deforested areas and forest fires in the State of Roraima from 2000 to 2010. We mapped de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 55 publications
2
32
0
3
Order By: Relevance
“…, Barni et al. ). In the 1997–1998 El Niño event, approximately 11,000 to 14,000 km 2 of forests were burned in the state of Roraima, an area equivalent to 7.4–9.0% of its forest cover and over twice as large as the total deforested area in the state up to 1997 (Barbosa and Fearnside ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…, Barni et al. ). In the 1997–1998 El Niño event, approximately 11,000 to 14,000 km 2 of forests were burned in the state of Roraima, an area equivalent to 7.4–9.0% of its forest cover and over twice as large as the total deforested area in the state up to 1997 (Barbosa and Fearnside ).…”
Section: Introductionmentioning
confidence: 99%
“…Barni et al. () estimated that 3.06 × 10 3 km 2 has been deforested and 3.02 × 10 3 km 2 of forests have burned between 2000 and 2010 in Roraima. These authors found that 98.5% of the forest area affected by fire was burned in years with El Niño events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above mentioned factors, the dynamics of the impacts of fire on savannas (Barbosa & Fearnside, 2005), and primary forests in Roraima State (Barni, Pereira, Manzi, & Barbosa, 2015) is, in part, a reflection of the long-established culture of slash-and-burn as a form of agricultural land management (Barbosa & Fearnside, 1999). This action has a singular impact on a local ecosystem, as it is associated with the effects of climate change (Gustavsson et al, 2017), and can increase the likelihood of extreme climatic events linked to either aridity or rainfall.…”
mentioning
confidence: 99%